Empowerment of Housewives in Utilizing Household Waste through Decoupage Handicrafts in Mokoau Village, Kendari City, Southeast Sulawesi - Satira Yusuf; Nur Irawati; Tuti Dharmawati (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
The problem faced by housewives  in Mokoau Subdistrict of  Kambu Kota Kendari is the lack of  creativity and productivity, whare the absence of  activities oriented  towoards economic independence limited capital to start a business and a lack of skills both and hard skills in the world of entrepreneurship. This resulted in housewives beings perceived as being less able to help the family economy. The solution offered is through entrepreneurial activities in the form of utilization of household waste in the form of used can and glass bottles combined with tissue decoupage handicrafts. Throught this activity is to increase the incamo of  housewives, especially in terms of utilization of  household waste, so that it general the economic empowerment of the community can also increase.